The Effect of Family Health Tasks on The Nutritional Status of Children Under Five Years Old With The Family-Centered Nursing Model Approach - Hidayati, Rina Nur; Ibnu, Faisal; Suwarsi, Suwarsi (Jurnal Keperawatan Respati Yogyakarta, 2025)
The fulfillment of family health duties is essential to improve the nutritional status of children under five years old. This study contributed to determining the influence of family health tasks on the nutritional status of children under five years old with the Family Centered Nursing (FCN) model approach. The Quasi-Experimental research design with the Pretest Posttest Nonequivalent Control Group Design approach with a sample of 150 people divided into 75 people in the intervention group and the control group. Data collection by measuring nutritional status (BB/U) from the Ministry of Health in 2020. Pre-test through measurement of nutritional status of children under five years old. The intervention was given for 8 weeks through a family health task intervention with the FCN model approach in the intervention group, and independent learning through modules in the dick group. Furthermore, a post-test is carried out through the measurement of the nutritional status of children under five years old. Data processing includes editing, coding, scoring, and tabulating, and then statistical tests are carried out for the Wilcoxon Rank Test. Results: There was a difference in the nutritional status of children under five years after being given the intervention in family health tasks. Family health tasks are effective in improving the nutritional status of children under five years old (P-v 0.025). Optimizing family health tasks with the FCN model approach is a strategic solution in public health programs that focus on improving the nutritional status of children under five years old.